2023
DOI: 10.3390/children10020230
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Retainers—A Critical Review

Abstract: The achievement of aesthetic, functional occlusion should not mark the end of the orthodontic intervention. To prevent relapse, retention needs advance planning, and may vary in duration. This review aims to present and comment on the available means of retention. The ever-popular, passive Hawley-like removable appliances are credible in maintaining the desired occlusion. Modifications are the removable appliance Wrap Around, having the labial archwire extending to the premolars; the translucent retainer, Asti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 127 publications
2
33
0
Order By: Relevance
“…Whereas, in case of VFRs it is not improving over the observation period of 12 months. This is in agreement with previous literature by Sauget et al (1997) [ 19 ] showing minimal improvement of teeth by R 1 retainers in vertical direction during retention phase. Recent studies by author like Dincer and Isik Aslan (2010) [ 22 ], Hoybjerg et al (2013) [ 20 ] too showed minimal improvement in vertical direction.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Whereas, in case of VFRs it is not improving over the observation period of 12 months. This is in agreement with previous literature by Sauget et al (1997) [ 19 ] showing minimal improvement of teeth by R 1 retainers in vertical direction during retention phase. Recent studies by author like Dincer and Isik Aslan (2010) [ 22 ], Hoybjerg et al (2013) [ 20 ] too showed minimal improvement in vertical direction.…”
Section: Discussionsupporting
confidence: 94%
“…HRs allows more vertical settling of posterior teeth than VFRs according to previous literature [ 19 , 20 ]. It has a demerit of wire component crossing occlusally, which has issue especially in extraction cases.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although efforts have been made through the years for the standardization of the retention protocol, this is impracticable. Every patient needs tailormade approaches according to their age, pre-treatment characteristics, periodontal and dental situation, compromises during treatment, compliance, etc., [ 12 , 74 , 75 , 76 ]. Knaup et al suggested the application of both removable and fixed appliances to enhance anterior teeth alignment stability over time [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…On-body devices refer to applications that are in direct contact with the skin, such as prostheses. They include the following medical fields dentistry [18, 115117], health care engineering [26, 27], general surgery [24, 25], oncology [42], oral and maxillofacial surgery [48, 50, 118], orthopedics [63, 74, 119125], otorhinolaryngology [78, 83], pediatrics [89], plastic surgery [93] and radiation oncology [44]. The organs or organ systems in this section include the cranium [44, 48, 78], musculoskeletal system [24, 44, 63, 74, 93, 119125], rectum [42], teeth [18, 115117] and trachea [124].…”
Section: Reviews In Medical 3d Printingmentioning
confidence: 99%